Clinical and Research Activities at the CATANA Facility of INFN-LNS: From the Conventional Hadrontherapy to the Laser-Driven Approach - Cirrone, Giuseppe A. P.; Cuttone, Giacomo; Raffaele, Luigi; Salamone, Vincenzo; Avitabile, Teresio; Privitera, Giuseppe; Spatola, Corrado; Amico, Antonio G.; Larosa, Giuseppina; Leanza, Renata; Margarone, Daniele; Milluzzo, Giuliana; et al. (Frontiers in Oncology, 2017)
The CATANA proton therapy center was the first Italian clinical facility making use of energetic (62 MeV) proton beams for the radioactive treatment of solid tumors. Since the date of the first patient treatment in 2002, 294 patients have been successful treated whose majority was affected by choroidal and iris melanomas. In this paper, we report on the current clinical and physical status of the CATANA facility describing the last dosimetric studies and reporting on the last patient follow-up results. The last part of the paper is dedicated to the description of the INFN-LNS ongoing activities on the realization of a beamline for the transport of laser-accelerated ion beams for future applications. The ELIMED (ELI-Beamlines MEDical and multidisciplinary applications) project is introduced and the main scientific aspects will be described.